DOTS-based tuberculosis treatment and control during civil conflict and an HIV epidemic, Churachandpur District, India - Rodger Alison J.; Toole Mike; Lalnuntluangi Baby; Muana V.; Deutschmann Peter (The World Health Organization, 2002)
OBJECTIVE: To pilot the WHO guidelines on DOTS for tuberculosis (TB) among displaced people affected by conflict in Churachandpur District, Manipur State, north-east India, which has endured an HIV epidemic, injecting drug use, civil unrest, high levels of TB, and poor TB treatment and prevention services for many years. METHODS: Prerequisites for TB control programmes were established. WHO guidelines and protocols were adapted for local use. Outreach workers were appointed from each ethnic group involved in the conflict, and training was conducted. Quality control and evaluation processes were introduced. FINDINGS: TB was diagnosed in 178 people between June and December 1998. Of the 170 with pulmonary disease, 85 were smear-positive. Successful outcomes were recorded in 91% of all patients and in 86% of smear-positive cases of pulmonary TB. The default rate and the mortality rate were low at 3% each. HIV positive serostatus was the only factor associated with a poor treatment outcome. CONCLUSION: TB treatment and control were possible in a conflict setting and WHO targets for cure were attainable. The factors associated with the success of the programme were strong local community support, the selection of outreach workers from each ethnic group to allow access to all areas and patients, the use of directly observed therapy three times a week instead of daily in the interest of increased safety, and the limiting of distances travelled by both outreach workers and patients.